THE IMPACT OF ORGANISATIONAL ON HUMAN RESOURCE MANAGEMENT IN SERVICE INDUSTRIES - Liu Xuewen; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
In practice, personnel managers often raise questions such as: "What exactly is the role of human resource management in the enterprise? Is it a service? Is it a strategic partner?" The essence of this question is the positioning of the enterprise's human resource management. As a unit that provides development support for the overall operation of an enterprise, the positioning of HRM necessarily depends on a variety of fundamental factors, such as the enterprise's organisational structure, business strategy, and type of enterprise. The organisational structure of an enterprise plays a decisive role in positioning its internal human resource management. In this paper, Enterprise System Management Consulting proposes positioning human resource management under different structures by sorting out the characteristics of the three primary organisational structures. Enterprises must change human resource management to adapt to environmental changes and realise sustainable development. With the development of enterprises, enterprise management has gone through the same stages: traditional, scientific, and modernised management. The core of modernised enterprise management is people-oriented management, and improving the strategic position of human resources in enterprise management is an important way for enterprises to flourish. This paper analyses the strategic position of the human resource department and its influencing factors from various perspectives.